The Role of Transformational Leadership in Fostering Community-Based Innovation for the Transformation of Residential Areas into the Jelita (Jepang Bali Kita) Village Tourism - Diana Claudya Gustafiani; Susi Hardjati (International Journal of Social, Economic, and Business, 2025)
This study examines transformational leadership's role in fostering community-based innovation to transform a residential area into the Jelita Tourism Village in Surabaya City. A qualitative research approach was employed, using a case study method. The research focuses on how community leaders demonstrate transformational leadership in initiating and sustaining the development of a tourism area based on citizen participation. The theoretical framework is based on the four dimensions of transformational leadership proposed by Bass & Riggio (2008): idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The findings reveal that the community leaders effectively implemented all four dimensions. Their ability to build a shared vision, encourage innovation, foster trust, and attend to both individual and group needs significantly contributed to increased community participation and the creation of innovations throughout the development process. This leadership style has proven to be a key factor in transforming the residential area into a sustainable, competitive, and culturally rooted tourism destination. The study underscores the importance of transformational leadership in community-based development and provides implications for similar communities in other regions.